Measuring Problem Solving with Technology: A Demonstration Study for NAEP - Bennett, Randy E; Persky, Hilary; Weiss, Andy; Jenkins, Frank (The Journal of Technology, Learning and Assessment, 2010)
This paper describes a study intended to demonstrate how an emerging skill, problem solving with technology, might be measured in the National Assessment of Educational Progress (NAEP). Two computer-delivered assessment scenarios were designed, one on solving science-related problems through electronic information search and the other on solving science-related problems by conducting simulated experiments. The assessment scenarios were administered in 2003 to nationally representative samples of 8th-grade students in over 200 schools. Results are reported on the psychometric functioning of the scenarios and the performance of population groups. Implications are offered for using online performance assessment to measure emerging skills in NAEP and other large-scale testing programs.